Is a Right Angle the Right Angle? Normal Coronal Radiographic Alignment in the Pediatric Finger Phalanges. Issue 8 (1st September 2021) - Krueger, Andrew; Qudsi, Rameez; Eckstein, Kendra; Cornwall, Roger
Abstract : Background: Quantifying pediatric phalanx fracture displacement requires understanding the normal radiographic alignment of pediatric phalanges, which has never been assessed in the coronal plane, although prior studies have assumed the articular surfaces and physes to be perpendicular to the diaphyses. This study tests the hypothesis that these relationships are not uniformly perpendicular and instead vary by digit and age. Methods: Normal hand bone age radiographs were retrospectively reviewed from 40 males and 40 females 2 to 18 years old. For each finger proximal phalanx (P1) and middle phalanx (P2), 2 raters each measured twice the angle between the diaphysis and distal articular surface (D-DA), diaphysis and physis (D-P, when physis present), and diaphysis and proximal articular surface (D-PA). Intra-rater and inter-rater reliability were calculated with intraclass correlation coefficients. 95% confidence intervals were calculated for each angle for each digit, phalanx, age group, and sex to determine which angles ~90 degrees. Variability among ages and sex was assessed with analysis of variance. Results: Intra-rater and inter-rater intraclass correlation coefficients were >0.90, except in P2 ∠D-DA in children under 8 years old with unossified P2 condyles. Overall, only 173 (47.8%) of 362 confidence intervals included 90 degrees. Three angles of the small finger (P1 ∠D-DA, P2 ∠D-P, P2 ∠D-PA) never ~90 degrees at any age or sex, with an average 10 degrees ulnar tilt of the small finger proximal interphalangeal joint. Of the 24 angles across digits and phalanges, 10 varied significantly with age, especially in the index and middle finger P1 where initially wedge-shaped epiphyses progressively became more symmetric with age. Conclusions: The coronal radiographic angles between the phalangeal diaphyses and articular surfaces or physes differ from 90 degrees more than half the time in pediatric fingers, and nearly half the angles vary by age. These findings demonstrate that the articular surfaces and physes of the pediatric finger phalanges are not uniformly perpendicular to the diaphyses, underscoring the need to consider the variability among digits, phalanges, ages and subjects. Level of Evidence: Level IV.